(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The main principles of education and training include the principle of educational education, the principle of awareness and activity, the principle of instruction, the principle of systematicity, and the principles of thoroughness. All these principles are interrelated.